Thyroid abscess secondary to infected synovial sarcoma of the thyroid: A case report (Indian Journal of Case Reports, 2025)
Primary sarcomas of the thyroid are very rare, accounting for <1.5% of all thyroid cancers. Due to its rarity and similarities to benign inflammatory conditions, diagnosing it accurately is challenging. We report a unique case of thyroid synovial sarcoma presenting like a thyroid abscess. A 50‐year‐old female presented with a painful, rapidly growing anterior neck swelling and fever over the past month. The neck mass measured 10 × 10 cm, was firm, mildly tender, and had erythematous skin. An enlarged right supraclavicular lymph node was also noted. Imaging showed a complex solid-cystic mass. Initial antibiotic treatment failed as the white blood cell count increased and fever persisted. Ultrasound-guided aspiration yielded hemopurulent fluid. Due to worsening sepsis, surgical drainage and open biopsy were performed. Histopathological analysis confirmed a diagnosis of synovial sarcoma, with immunohistochemistry showing positivity for transducin-like enhancer 1, cytokeratin, B-cell lymphoma, epithelial membrane antigen, and CD99. This case highlights the need to consider rare sarcomas when diagnosing thyroid abscesses, especially if standard treatments fail. Early and precise diagnosis through histopathological and molecular tests is vital for determining the best treatment approach. The literature suggests that early recognition and intensive multimodal management may improve outcomes for this rare but aggressive cancer.